RISK MANAGEMENT STRATEGIES ON HIGH-RISE BUILDING PROJECTS IN THE INDONESIAN CONSTRUCTION INDUSTRY - Faizal Addin Achmad (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
The high-rise building construction industry in Indonesia faces technical and non-technical risks such as work safety, delays, cost overruns, and contract conflicts. This research examines risk management strategies in high-rise building projects with reference to ISO 31000 in the BTN Bank Building project in the Kelapa Gading area of North Jakarta, through literature studies and analysis of actual project cases in Indonesia. The results show that the initial stages of risk management have been implemented, but full implementation is still not optimal. The main risks include delays in material supply, work accidents, and limited human resources risk experts. Mitigation strategies implemented include avoidance, risk transfer, and impact reduction. The main barriers are reactive organizational culture, lack of documentation, and limited management support. This research recommends the integration of risk management in the project management system and the improvement of HR competencies to increase project success and construction industry efficiency.